The Present Situation of the Libyan Accounting Research from the Perspective of Faculty Members in the Accounting Departments in Economics Faculties in the Universities of Tripoli, Zawiya and Sabratha - The Present Situation of the Libyan Accounting Research from the Perspective of Faculty Members in the Accounting Departments in Economics Faculties in the Universities of Tripoli, Zawiya and Sabratha (University of Science and Technology, Yemen, 2020)
This study aimed to investigate the present situation of the Libyan accounting research by assessing the availability of appropriate characteristics in its three components (research - researcher - research environment). To achieve this, the descriptive method was followed, and (75) questionnaires were distributed in electronic and paper form to a random sample of faculty members in the accounting departments of the Faculties of Economics in the universities of Tripoli, Zawiya and Sabratha, but (57) questionnaires were valid for statistical analysis using the (SPSS) program. Major findings revealed the availability of the characteristics of research in the published Libyan accounting research, as well as the availability of the characteristics of researchers in the Libyan accounting researcher with means of (3.126) and (3.175) respectively. Further, findings showed lack of appropriate research environment characteristics in the Libyan accounting research environment. The study recommended improving the characteristics of accounting research by setting conditions for writing and publishing accounting research, coordinating lists of scientific journals in which it can be published, and supporting the accounting researcher by reducing their teaching burden, activating sabbaticals and preparing specialized training programs to develop their research skills. In addition, independent and sufficient budgets for accounting research should be allocated to create an environment for scientific accounting research.